The Avdat in Late Antiquity Project: uncovering the Early Islamic phases of a Byzantine town in the Negev Highlands. (June 2022) - Bucking, Scott; Fuks, Daniel; Dunseth, Zachary C.; Schwimer, Lior; Erickson-Gini, Tali
Abstract: Abstract : Three seasons of archaeological fieldwork by the Avdat in Late Antiquity Project have yielded new evidence of intensive Early Islamic activity in the late antique town of Avdat in Israel's Negev Highlands. This evidence has important implications for understanding the fate of such towns in the region during the Byzantine–Islamic transition.